2015
DOI: 10.1128/aem.00518-15
|View full text |Cite
|
Sign up to set email alerts
|

Vibriophages Differentially Influence Biofilm Formation by Vibrio anguillarum Strains

Abstract: Vibrio anguillarum is an important pathogen in marine aquaculture, responsible for vibriosis. Bacteriophages can potentially be used to control bacterial pathogens; however, successful application of phages requires a detailed understanding of phage-host interactions under both free-living and surface-associated growth conditions. In this study, we explored in vitro phage-host interactions in two different strains of V. anguillarum (BA35 and PF430-3) during growth in microcolonies, biofilms, and freeliving cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 46 publications
6
45
0
Order By: Relevance
“…Overall, our results confirm the link between enhanced biofilm formation and lysogeny424344 or exposure to lytic phages at concentrations that do not eradicate the population4546. In the case of lytic phages, a study by Hosseinidoust et al 45.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, our results confirm the link between enhanced biofilm formation and lysogeny424344 or exposure to lytic phages at concentrations that do not eradicate the population4546. In the case of lytic phages, a study by Hosseinidoust et al 45.…”
Section: Discussionsupporting
confidence: 82%
“…By contrast, cells that survived exposure to phage KVP40 always multiplied to produce offspring that had regained phage sensitivity (7, 12). Therefore, we suggest that the sensitivity to phage KVP40 was related to regulation of phenotypic traits rather than genetic mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Vibrio anguillarum phages have been shown to have different influences on biofilm formation over long-term cultures, due mostly to varied microcolony morphologies with one strain having flat single layers (BA35), and the other forming complex 3D structures (PF430-3) [87]. This structural distinction resulted in differential penetrability of the biofilm structure by phages during the initial stages of biofilm formation, and ultimately impeded the formation of the BA35 single layer biofilm compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Phage infection of BA35 resulted in a large percentage of resistant mutants (~70% of isolated cells); however, PF430-3 formed more complex 3D structures in the presence of its lytic phage, resulting in fewer resistant mutants. This result suggested that aggregation within these structures could be reducing phage adsorption [87]. The phage particles appeared to be trapped within the aggregate matrix, a complex consortia of extracellular polymeric substances of unknown composition that seemingly provided physical protection against phage infection; the mechanism for this differential aggregation phenotype has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%